Effect of Mudharabah, Musyarakah and Murabahah Financing on Profitability of Islamic Banks Listed on the Indonesia Stock Exchange for the 2018-2020 Period - Sri Wulan Dari; Imelda Dian Rahmawati (Indonesian Journal of Islamic Studies, 2022)
Based on the objectives of this research, including to determine the effect of mudharabah on profitability in Islamic banks listed on the Indonesia Stock Exchange for the 2018-2020 period. To determine the effect of Musyarakah on Profitability of Islamic Banks Listed on the Indonesia Stock Exchange for the 2018-2020 period. To determine the effect of Murabaha on Profitability of Islamic Banks Listed on the Indonesia Stock Exchange for the 2018-2020 period. The research method used is quantitative. The population is taken from the data of Islamic banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling is Saturated Sampling. The population has 42 financial reports from 14 Islamic banking companies multiplied by 3 years. Data retrieval is done by using documentation taken from the financial statements. This study uses data analysis, namely multiple linear analysis with the SPSS (Statistics Program For Social Science) program and hypothesis testing using the t test. The results show that Mudharabah Financing has a positive and significant effect on profitability in Islamic banking companies. Musyarakah financing has a positive and significant effect on profitability in Islamic banking companies. And Murabahah Financing has a positive and significant effect on profitability in Islamic banking companies.